Blue fingers : a ninja's tale - Whitesel, Cheryl Aylward (Clarion Books, 2004)
Having failed apprenticeship as a dye maker, Koji is captured and forced to train as a ninja, where he remains disloyal until he discovers samurai have burned his former village.